1985
DOI: 10.1111/j.1651-2227.1985.tb10096.x
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis precursors in Finnish children and adolescents. XIV. Zinc and copper concentrations in deciduous teeth

Abstract: land). Atherosclerosis Precursors in Finnish children and adolescents. XIV. Zinc and copper Concentrations in deciduous teeth. Acta Paediatr Scand Suppl. 318: 213, 1985. Zinc and copper concentrations were analysed from cariesfree deciduous teeth of 125 Finnish children, 6-7-and 9-10-year-olds, from three cities. Enamel and dentine were separated and prepared into pills which were analysed individually with the proton induced x-ray emission spectrometry (PIXE) method. The total mean ( f SD) zinc concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The median concentration of Pb in teeth of children living in Brazil (Gomes et al 2004) was found to be 169 μg/g from the industrial area and 118 μg/g from the children living far from the industry. The average concentrations of Zn in Finnish children were 143 and 133 ppm for enamel and dentine, respectively, and the median Cu concentrations for enamel and dentine were 0.54 and 0.27 ppm, respectively (Haavikko et al 2008). The average concentrations of Pb, Cu, Fe, and Zn in human teeth from Poland were 17.1, 4.4, 46.6, and 802.2 μg/g, respectively (Baranowska et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The median concentration of Pb in teeth of children living in Brazil (Gomes et al 2004) was found to be 169 μg/g from the industrial area and 118 μg/g from the children living far from the industry. The average concentrations of Zn in Finnish children were 143 and 133 ppm for enamel and dentine, respectively, and the median Cu concentrations for enamel and dentine were 0.54 and 0.27 ppm, respectively (Haavikko et al 2008). The average concentrations of Pb, Cu, Fe, and Zn in human teeth from Poland were 17.1, 4.4, 46.6, and 802.2 μg/g, respectively (Baranowska et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The levels of elements that are lower in the teeth of control subjects from Mysore than that of other investigations [11,[21][22][23] are indicative of low levels of environmental exposure to heavy metals. Likewise, low levels of Pb-T were reported in the 9-year-old children from two (Helsinki and Kuopio) Finnish towns [6].…”
Section: Quality Control Studiesmentioning
confidence: 56%
“…In the case of nutritional elements, low Cu-T levels detected in the hypertensive subjects of Mysore and Finnish children with atherosclerosis [11] may be attributed to nutritional implication. It is, therefore, viewed that human teeth may indicate low status of essential trace elements.…”
Section: Quality Control Studiesmentioning
confidence: 96%
See 2 more Smart Citations